A four-year investigation of the seropositivity of Toxoplasma gondii in our hospital - Kuk, Salih; Ozden, Mehmet (My University, 2007)
Toxoplasma gondii is an obligate intracellular parasite occurring in both animals and humans throughout the world. Infection with Toxoplasma gondii can lead to congenital and acquired disease. Different techniques for the diagnosis of this disease have been used. The aim of this study was to determine the prevalence of IgG and IgM antibody to Toxoplasma gondii in patients. This study was carried out between 1999 and 2003; antibody titers were detected by ELISA in the sera of 4908 patients. The results showed that 1522 (31.01%) patients were IgG positive, and 38 (0.77%) patients were IgM positive with the ELISA test. Besides this, T. gondii specific IgG antibody was found in 171 (31.09%) newborn patients.
Hastanemizde dört yillik Toxoplasma gondii seropozitifli?inin araştirilmasi.
Keywords: Animals; Antibodies, Protozoan; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin G; Immunoglobulin M; Infant, Newborn; Male; Seroepidemiologic Studies; Toxoplasma; Toxoplasmosis; Toxoplasmosis, Congenital; Turkey; immunoglobulin G; immunoglobulin M; protozoon antibody; animal; article; blood; congenital toxoplasmosis; enzyme linked immunosorbent assay; epidemiology; female; human; immunology; male; newborn; Toxoplasma; toxoplasmosis; Turkey (republic)